Readiness Level of Elementary Schools in Berkoh Purwokerto Selatan, in Implementing E-Learning during the Pandemic - Takris, Muhamad Kris; Andriani, Ana Andriani (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2022)
Abstract. The Covid-19 pandemic has an impact on the world of education, namely the use of technology for learning. This study aims to determine the level of readiness of E-Learning in three elementary schools in the Berkoh Village. Survey research method, using a sample for the entire population. Participants come from the principal and teachers. The questionnaire instrument was used to measure the readiness to use learning technology, the readiness of infrastructure in schools, the readiness of school organizations, and additional information. Retrieval of data as much as 15 samples from 21 total populations. Data processing techniques and data analysis using descriptive statistical methods. From the four indicators of readiness, Of the four indicators of readiness coded into a readiness value. Results SDN 1 Berkoh Not ready needs a lot of work, SDN 2 Berkoh is Ready but needs a few improvement, and SDN 3 Not ready needs some of work